Rethinking privatization policies in education: The enclosure of the school - Noelia Fernández-González (Arizona State University, 2016)
This article aims to introduce the concept of enclosure as a category to think about privatization policies in education. The concept of enclosure refers to the process by which communal land rights and uses were removed between the 14th and 18th centuries, making possible the passage from feudalism to capitalism. Nowadays, a discourse named as a "commons paradigm" (Bollier, 2007) exposes privatization dynamics as a contemporary movement of enclosure. This paradigm stablishes an analogy between the enclosures that made possible the primitive accumulation and the contemporary dynamics of privatization. In this text, privatization policies in education are analyzed as a movement of enclosure in the school. The text is divided into four sections. Firstly, it analyzes the state-reform process in the current context of globalization and the blurring of boundaries between the public and the private. Secondly, it focuses in the "commons paradigm", followed by its critics in the next section. The fourth section reflects on the enclosure of the school taking as starting point previous research about privatization policies introduced in Spain and particularly in the Autonomous Region of Madrid.